Kajian Program Misykat (Microfinance Syariah Berbasis Masyarakat) Sebagai Alternatif Pilihan Program Pemberdayaan Usaha Mikro (Studi Kasus pada Dompet Peduli Umat Daarut Tauhid Bogor) - Aulie Tsalistia; Rizal Syarief; - Suryahadi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2010)
One of the alternative institution that distributes productive fund to the community in need is the “Amil Zakat” Institution.  The community-based Misykat, which belongs to the institution, is Dompet Peduli Umat Daarut Tauhid (DPUDT), which not only contributes the rolling fund but also establishes mental and character building as its main product. It also delivers business management to a self-supporting community, and  create a new working environment for the local community. The objectives of this study are, firstly, to analyze the implementation of the Misykat Program for the empowerment of micro-businesses in Bogor, based on the achievement of the program, and secondly, to analyze the most influencing strategy of the Misykat Program in Bogor, based on the priority scale.  The data collecting was conducted through literature study, standard operation of the Misykat Program, and data implementation of the program in Bogor as the secondary data collecting.  The primary data collecting was obtained through interview with the management, and through questionnaire input from members. The data analysis was executed through the descriptive and Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis using Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) and SWOT matrix.  The last stage of the strategy formulation was the decision in using the Quantitative Strategic Planning (QSP) matrix. The study showed that 30 people joined the Misykat Program, and that there were still no significant changes in the economic welfare of its members.  However, there was an increase in the accumulation of members’  saving and reserved fund, and their economic productivity, caused by a creativity enhancement in developing business.  In the Nurul Qomar Council, the distributed fund was more effective compared to that in the Al-Ikhlas Council. There was a paradigm shift in the members’  way of thinking as a result of an intensive community establishment.  Unfortunately, no member has become “Muzakki” yet because their earnings have not reached “nishab”.  Meanwhile, the most applicable strategies are enhancing the quality of service, education and supervision to the members